Physicochemical factors affecting mangrove distribution and occurence in selected sites in the province of Iloilo. - Pedrola, Kimberly Anne Sta. Maria (2006.)
Mangrove is a type of forest growing along tidal mudflats and along shallow water coastal areas extending inland along rivers streams and their tributaries where the water is generally brackish. The objective of this study is to determine the physicochemical factors influencing the distribution and occurence of mangroves in selected sites in the Province of Iloilo and to correlate these factors using Pearson Correlation Coefficient. There were 122 plots established in five municipalities in the province of Iloilo. 51 plots were established in Ajuy; 26 plots in Balasan; 13 plots in Barotac Viejo; 26 plots in Estancia; and 6 plots in Tigbauan. There was a total of 18 true mangrove species belonging to the 11 families was found in the five municipalities of Iloilo. The 11 families are Family Avicenniaceae presented by A. alba, A. marina, A. officinalis, & A. rumphiana; Family Bombacaceae presented by C. philippinensis; Family Combretaceae presented by L. racemosa; Family Euphorbiaceae presented by E. agallocha; Family Meliaceae presented by X. mollucenensis; Family Myrsinaceae presented by O. octodonta; Family Palmae presented by N. fruiticans; Family Rhizophoraceae presented by B. cylindrica, C. decandra, R. apiculata, R. mucronata, & R. Stylosa; Family Rubiaceae presented by S. hydrophyllacea; & Family Sonneratiaceae presented by S. alba. For Water pH, the highest value of 7.5 was observed in Ajuy & the lowest value of 6.66 in Tigbauan with an overall mean of 7.22. For salinity, the highest value of 36.44 percent was observed in Ajuy & the lowest value of 22.92 percent in Balasan with an overall mean of 30.97 percent. For Water Temperature, the highest value of 28.69 centigrade was observed in Barotac Viejo & the lowest value of 26.33 centigrade in Tigbauan with an overall mean of 27.5 centigrade. For Soil Temperature, the highest value of 29.34 centigrade was observed in Barotac Viejo & the lowest value of 26.8 centigrade in Tigbauan with an overall mean of 27.69 centigrade. The species R. apiculata (r=0.783365) was positively correlated with salinity (favor high salinity); S. alba with water (r= 0.96326) and soil (r= 0.986391) temperatures (favor high temperature); E. agallocha (r=-0.91066) was negatively correlated with pH (favor high pH), water (r=-0.81886) and soil (r= -0.95557) temperatures (favor low temperature); Nypa, (r=-0.94652) A. officinalis (r=-0.97923) and A. rumphiana (r=-0.93921) were negatively correlated with salinity (favor low salinity); and C. philippinensis was negatively correlated with water (r=-93442) and soil (r=-0.8498) temperatures (prefer low temperature). Avicennia marina showed wider tolerance for pH (r=-0.02443), salinity (r=0.638945), and water (r=-046877) and soil (r=-0.49251) tempratures.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Mangroves -- Iloilo Province